Should Modest Elevations in Prostate-Specific Antigen, International Prostate Symptom Score, or Their Rates of Increase Over Time be Used as Surrogate Measures of Incident Benign Prostatic Hyperplasia? - Schenk, Jeannette M. (Oxford University Press, 2013)
Although surrogate measures of benign prostatic hyperplasia (BPH) are often used in epidemiologic studies, their performance characteristics are unknown. Using data from the Prostate Cancer Prevention Trial (n = 5,986), we evaluated prostate-specific antigen (PSA), International Prostate Symptom Score (IPSS), and their rates of change as predictors of incident BPH. BPH (n = 842 cases) was defined as medical or surgical treatment or at least 2 IPSS of 15 or higher. Proportional hazards models were used to measure the associations of baseline PSA, IPSS, and their velocities over 2 years with BPH risk, and time-dependent receiver-operating characteristic curves were used to measure their discriminatory performance. Unit increases in PSA, IPSS, and IPSS velocity were associated with 34%, 35%, and 29% (all P < 0.001) increases in BPH risk, respectively. The areas under the receiver-operating characteristic curves were significantly greater than 0.5 for PSA (0.58, 95% confidence interval (CI): 0.56, 0.60), IPSS (0.77, 95% CI: 0.75, 0.78), and IPSS velocity (0.63, 95% CI: 0.61, 0.65); however there were no cut points at which sensitivity and specificity were both above 75%. We concluded that moderate elevations in PSA, IPSS, or their rates of change should not be used as surrogate measures of incident BPH.